1997
DOI: 10.1136/oem.54.1.44
|View full text |Cite
|
Sign up to set email alerts
|

People can detect poor air quality well below guideline concentrations: a prevalence study of annoyance reactions and air pollution from traffic.

Abstract: Objectives-Motor vehicle exhaust fumes are the main source of atmospheric pollution in cities in industrialised countries. They cause respiratory disease and annoy people exposed to them. The relation between ambient exposure to air pollution mainly from motor vehicles and annoyance reactions in a general population was assessed. Also, the importance of factors such as age, sex, respiratory disease, access to the use of a car, and smoking habits on the reporting of these reactions was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 13 publications
4
74
2
3
Order By: Relevance
“…These results do, however, not necessarily apply to the office condition, since the removal rate of pollutants by plants is much slower than that of an optimally functioning ventilation system [11]. On the other hand, a minor change in the content of air contaminants might have a positive influence on the employees' perception of comfort [12] and thereby result in a lower score for the reported health and discomfort symptoms. The symptoms chosen for this study are known to be affected by indoor air quality [2,9,13,14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results do, however, not necessarily apply to the office condition, since the removal rate of pollutants by plants is much slower than that of an optimally functioning ventilation system [11]. On the other hand, a minor change in the content of air contaminants might have a positive influence on the employees' perception of comfort [12] and thereby result in a lower score for the reported health and discomfort symptoms. The symptoms chosen for this study are known to be affected by indoor air quality [2,9,13,14].…”
Section: Discussionmentioning
confidence: 95%
“…The subjects completed a questionnaire every 2nd week about 12 different health symptoms during two spring periods of 3 months in 1995 and 1996. The questionnaire, which was modified after Anderson et al [9], included questions on the following 12 symptoms: (1) fatigue, (2) feeling heavy-headed, (3) headache, (4) nausea/drowsiness, (5) concentration problems, (6) itching, burning, irritation of the eyes, (7) irritated, stuffy or 'running' nose, (8) hoarse, dry throat, (9) cough, (10) dry or flushed facial skin, (11) scaling/itching scalp or ears, (12) hands with dry, itching, or red skin. Each symptom could be given one of the following scores: 0 (no problems), 1 (minor problems), 2 (moderate problems) or 3 (severe problems).…”
Section: Methodsmentioning
confidence: 99%
“…However, in another Swedish study, correlations were demonstrated between respiratory symptoms in symptomatic adults and daily variations in relatively low concentrations of NO 2 [32]. In addition, in a Swedish cross-sectional study with population samples from 55 towns and cities, annoyance reactions [33] as well as frequent respiratory symptoms [11] were associated with six-monthly average concentrations of NO 2 , while NO 2 was nonsignificant in a similar diary study from Piteå [8]. However, the NO 2 concentration was 1.5-fold higher in Landskrona than in Piteå.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to environmental health it is important to understand how soundscapes are affected by exposures to other ambient stressors such as air pollution. To this end, previous research has also demonstrated doseeresponse relationships between common air pollutants and odour annoyance at exposure levels well below most regulatory guidelines (Atari et al, 2012;Forsberg et al, 1997;Klaeboe et al, 2008). Taken together with the soundscape perspective and previously demonstrated noise annoyance dose-responses, this suggests that there may be an interaction effect between noise and odours on noise annoyance and that absolute levels of noise annoyance depend on environmental context.…”
Section: Introductionmentioning
confidence: 68%